Adaptive stabilization of a class of time-varying systems with an uncertain delay. Issue 3 (September 2016) - Gaudette, Darrell; Miller, Daniel
Abstract Handling delays and uncertain parameters in control systems is an interesting and challenging class of problems. In this paper, we consider the problem of "bounded-input bounded-output stabilizing" a class of single-input single-output, linear time-varying plant models with a time-delay margin as large as desired and a considerable amount of uncertainty in the input matrix of the state-space model. The proposed controller, while periodic and mildly nonlinear, is of low complexity; it tolerates slow variations in the delay and the elements of the input matrix as well as occasional jumps in these parameters, and guarantees that the effect of the initial condition decays exponentially to zero, even in the presence of noise.